Isolation and identification of GABA-producing lactic acid bacteria from fermented foods - Krongkeha, Watcharacha (RMUTSB ACADEMIC JOURNAL, 2022)
GABA, gamma aminobutyric acid, is a neurotransmitter, which can be naturally produced by lactic acid bacteria that are commonly found in fermented foods. The purpose of this research was to isolate and identify potential strains of lactic acid bacteria that can produce GABA from 2 different types of fermented food products, namely Nham and Pla Som. MRS agar medium containing 5% monosodium glutamate (MSG) and 0.50% calcium carbonate (CaCO3) was used for bacterial isolation. Forty isolates of lactic acid bacteria were tested for GABA production in MRS broth containing 5% MSG. All isolates of lactic acid bacteria were able to produce GABA. Four isolates were selected, namely N1-2, N2-9, F1-4 and F2-6, due to high capability of GABA production at the maximum amounts of 0.13, 0.05, 0.04 and 0.02 mg/10g, respectively. They are Gram-positive bacteria. The N1-2 and F1-4 isolates are bacilli. The N2-9 and F2-6 isolates are short bacilli and cocci. The results of nucleotide sequences of the 16S rRNA genes revealed that N1-2 was identified as Lactobacillus plantarum. F1-4 could be identified as Lactobacillus pentosus. In addition, N2-9 and F2-6 were identified as Weissella paramesenteroides. Therefore, the selected lactic acid bacteria have the potential to be developed as a starter culture in the fermented food industry.